An interesting study of personal and property rights of parents and children - Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Review of the monograph of L. Krasitsky "Problems of realization and protection of personal and property rights of parents and children."